Single-Breath Counting: An Alternative to Evaluate the Evolution of Pulmonary Function in the Postoperative Period of Cardiac Surgery (Global Journal of Medical Research, 2020)
Purpose: To evaluate the evolution of lung function through Slow Vital Capacity (SVC) and Single-breath Counting (SBC) in the cardiac surgery's period postoperative, evaluating a possible correlation between the technics. Methods: Longitudinal research, 18 to 80 years old patients. SVC and SBC were randomly evaluated. The SVC was measured using the ventilometer. To evaluate the SBC, the patients was instructed to breathe deepest possible and then breathe out while counting in ascending order trying to arrive in the larger number possible in a unique exhale. Was realized three repetitions. The SVC and the SBC were evaluated daily until discharge from the hospital. Results: Twenty-four patients completed the protocol. The evaluations were done during at least six days. There was a progressive increase in SVC (Day one: 1,0#xB1; 0,2L vs day six: 1,3 #xB1; 0,3L; p lt;0,05) and SBC Day one: 11,7 #xB1; 7 vs day six: 24 #xB1; 7;, p lt;0,05). Beyond positive correlation from moderate to strong between both techniques from second to fifth day, in relative ideal weight form, and from second to sixth day in absolutely form of the SVC.
Keywords: vital capacity phonation surgery cardiac